2020
DOI: 10.1111/evo.14133
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic pleiotropy can promote adaptation to patchy environments*

Abstract: How do gene variants with opposing effects on fitness in juvenile and adult insects perform in different ecological settings? Marden et al. used alleles of two antagonistic genes involved in metabolism and oxygen sensing in the Glanville fritillary butterfly as a model to demonstrate how these genes can antagonistically affect larval development and the adaptation of adults to different landscapes. This paper provides a case study for understanding how antagonistic pleiotropy can contribute to species adaption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The identification of modifier genes is challenging since they can only be comprehended in a network context 54 . Pleiotropic effects associated with adaptation to a new environment, a field where an insecticide is constantly sprayed, for example, can be found in the literature 28,55–57 . However, pleiotropic effects are not always granted to resistance mutations, they may be a consequence of other natural occurring mutations whose frequency depends on the environment 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of modifier genes is challenging since they can only be comprehended in a network context 54 . Pleiotropic effects associated with adaptation to a new environment, a field where an insecticide is constantly sprayed, for example, can be found in the literature 28,55–57 . However, pleiotropic effects are not always granted to resistance mutations, they may be a consequence of other natural occurring mutations whose frequency depends on the environment 58 .…”
Section: Discussionmentioning
confidence: 99%
“…54 Pleiotropic effects associated with adaptation to a new environment, a field where an insecticide is constantly sprayed, for example, can be found in the literature. 28,[55][56][57] However, pleiotropic effects are not always granted to resistance mutations, they may be a consequence of other natural occurring mutations whose frequency depends on the environment. 58 Results indicated that the fitness cost observed in the RR strain is not caused by pleiotropic effects of resistance genes, otherwise the Iso-RR strain would also present a fitness cost associated with diamides resistance.…”
Section: Discussionmentioning
confidence: 99%